Kepedulian Orang Tua terhadap Kegiatan Belajar Anaknya di Desa Segati Kecamatan Langgam Kabupaten Pelalawan - Feni Fitria; Said Suhil Achmad; Muhammad Jais (Fakultas Syariah IAIN Laa Roiba Bogor, 2023)
The purpose of this study was to find out how parents care about their children's educational activities in Segati Village, Langgam District, Pelalawan Regency. The type of research used in this study is qualitative descriptive research. The qualities have been proven to examine various problems in the field and find a context that is more suitable for the conditions in which this study was conducted. The results of this study are that there are 6 indicators of parents' concern for their children's learning activities, namely attention, love, affection, help, interference and behavior. Then the following conclusion can be drawn: It can be seen from the fact that parents are very concerned about their children's learning activities. Parents pay attention to their children such as delivering children to school, paying attention to their learning needs such as school clothes, shoes, school bags and providing children's learning facilities in the form of stationery with the aim of making children more pinned. Keywords: